Infantile tremor syndrome - Brahmbhatt, Vihang; Patel, Panna; Brahmbhatt, Shruti (International Journal of Contemporary Pediatrics, 2016)
Infantile tremor syndrome (ITS) is a clinical entity characterized by tremors, skin pigmentation, anemia, developmental and mental retardation. It is most commonly found in Indian subcontinent and in children who are exclusively on breast feeding of vegetarian mother. Amongst all the etiological theories, nutritional theory is the most accepted one. Management of ITS is largely empirical and includes therapy of nutritional deficiency, anemia & tremors apart from appropriate care. Treatment of nutritional deficiency includes vitamin B12, multivitamins, folic acid, iron, calcium, zinc, magnesium and high protein diet. In this article, three cases of ITS with classical picture have been reported.